2011
DOI: 10.1260/0958-305x.22.7.891
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Air Quality Status of Bonny Island, Nigeria Attributed to an Lng Plant

Abstract: The Bonny Island axis of the Niger Delta, Nigeria, is one of the most industrialized belts of Nigeria. Among the significant industries in the locality is the Nigerian natural gas liquefying plants. The plant complex generates emissions which are propagated by meteorological agents. An atmospheric dispersion model was used to model the emissions using a computer programme. A statistical analysis of meteorological parameters was also carried out to determine the pollutants dispersion in the atmosphere. The anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Therefore in one hour, pollutants will be transported 10.8 km. This also supports calculations by [16] that pollutants are transported to distant areas far from their sources within the region.…”
Section: Suspended Particulatesupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore in one hour, pollutants will be transported 10.8 km. This also supports calculations by [16] that pollutants are transported to distant areas far from their sources within the region.…”
Section: Suspended Particulatesupporting
confidence: 89%
“…We have briefly overviewed the sources of emissions that impact on the air quality of the region. The location of a specific activity-form is likely to be associated with the potential air quality of its immediate vicinity and even beyond [15] [16]. The presence of heavy industries raises the level of atmospheric contamination in the region; likewise the sprawling urban centres and traffic congestion.…”
Section: Sources Of Emissions That Impact the Regional Air Qualitymentioning
confidence: 99%
“…Adoki (2012) expressed units as µg/m3. Ede et al (2011) expressed units as g/sec (emission rate), Ibe et al (2020) expressed units of VOC as mg/m3, and (NO2 and SO2); Onakpohor et al (2020), Weli & Adekunle (2014) expressed the units as mg/m3, Akpan (2016) presented the values as carbonate (as CO2), sulphate (SOx), nitrate (NO3), and CO; * and ** in the rows are dry and wet seasons respectively. SOx, NOx, and CO: the limits were expressed as a daily average of 1 hourly value.…”
Section: Sulfur Dioxide and Hydrogen Sulfidementioning
confidence: 99%
“…Carbon monoxide monitoring is routine in the Niger Delta compared to carbon dioxide. Different concentrations of carbon monoxide exceeding the FEPA permissible limits occur in other regions in the Niger Delta, especially in artisanal crude oil refining areas (Onakpohor et al, 2020), natural gas liquefying plants (Ede et al, 2011), gas flaring (Akpan, 2016), built areas and forest swamps (Obisesan, 2019) (Table 2). Furthermore, a few studies have reported a high concentration of carbon dioxide in the Niger Delta region of Nigeria.…”
Section: Carbon Oxidesmentioning
confidence: 99%
“…Crops cultivated 2 km away from gas-flared points are usually scorched by the heat emitted from the gas flares (Anomohanran 2012). Particulates from gas flares can spread as far as 2.61 Â 10 6 km away from flare points (Ede et al 2011). A study conducted by Gobo et al (2009) revealed that these pollutants could trigger onset of eye, skin, and respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%